Effect Of Dry Conditions on The Formation of Plastid Pigments of Annual Rye (Secale Cereale L.) Cultivars - Makhramova M.Sh; Urokov S.X (Zien Journals, 2023)
Rye ( Secale cereale L.) is one of the most useful cereal plants. Rye products contain many biological substances necessary for human health. It contains carbohydrates, proteins, fats, phosphate salts, various macro and microelements, vitamins of group B, PP,E, A and other vitamins are found. There are many benefits of rye for the national economy . In agriculture, rye flour is used for bread, grain for animal feed, and green plant for pasture. Rye has several advantages over other plants . It is a much more cold - resistant plant than wheat . It has been found that many useful plants can grow in low sandy soils. In addition, the advantage of rye over other cereal plants is that it is considered as one of the plants that is more resistant to drought. Drought tolerance is the ability of a plant to maintain is physiological characteristics without significant changes in drought conditions. The resistance of rye to drought is related to its physiological conditions. Because its root system has the ability to absorb water well. However, drought affects almost all physiological indicators of rye. It also causes a change in the amount of plastid pigments formed in its leaves. Under normal conditions the amount of chlorophyll a pigments in rye leaves is more than other pigments. But in arid environments, its possible to see a significant decrease in their production. Synthesis of chlorophyll b and carotenoids in leaves was found to be significantly reduced under drought conditions.
Keywords: rye; phenological stages; water deficit; pigments